1993
DOI: 10.1177/0959353593031002
|View full text |Cite
|
Sign up to set email alerts
|

Meeting at the Crossroads: Women's Psychology and Girls' Development

Abstract: For over a century, psychologists have described adolescence as a time of heightened psychological risk for girls. This article explores a relational impasse or crisis of connection that we have observed in girls' lives at adolescence by tracing through time the thoughts and feelings of two 12-year-old girls who were interviewed as part of a 5-year longitudinal study of girls' psychological development. Using a voice-centered relational method, we join the experiences of struggle and resistance at this develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
776
5
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 636 publications
(805 citation statements)
references
References 12 publications
15
776
5
9
Order By: Relevance
“…There are some suggested methods for data analysis to enable researchers to fully engage in the reflexivity process and to address the risk of bias in womancentred research. Mauthner and Doucet (1998) describe their use of the voice-centred relational method of data analysis developed by Brown and Gilligan (1992) in order to demonstrate a meaningful use of reflexivity. They state that few researchers fully offer reflexive accounts of data analysis.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…There are some suggested methods for data analysis to enable researchers to fully engage in the reflexivity process and to address the risk of bias in womancentred research. Mauthner and Doucet (1998) describe their use of the voice-centred relational method of data analysis developed by Brown and Gilligan (1992) in order to demonstrate a meaningful use of reflexivity. They state that few researchers fully offer reflexive accounts of data analysis.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…However, only some of the girls experienced any success as a result or were supported in their efforts. Brown and Gilligan (1992) pointed out that resistance to social expectations is related to a faith that the current social organization will offer some protection against potential harsh social consequences, which suggests that losing faith in the system's capacity or protection would undermine the ability to resist. Brown and Gilligan found that girls who had close, open, and often overtly conflictual relationships with their parents, their mothers in particular, were able to maintain the ability to resist-to be a social critic and to give voice to their own experience.…”
Section: Maintaining Proactive Strategiesmentioning
confidence: 99%
“…For adolescent girls, saying what they think and feel often represents social risks, such as the risk of losing relationships (status) and finding themselves powerless and alone (Brown & Gilligan, 1992). Brown and Gilligan (1992) suggested that as this happens, resistance to their social situation turns inward and manifests as dissociation and not knowing, and undermines their potential for engaging in open conflict.…”
Section: Interaction Sexual Objectification Of Breasts and The Opprmentioning
confidence: 99%
See 2 more Smart Citations